The Effect of Busy Box Media on Early Childhood Counting Skills - Sri Pujianti, Eka; Pujiarto (Kirana Publisher (KNPub), 2024)
The use of Busy Box media can be an alternative learning medium. The aspect of development that can be developed through Busy Box media is children's cognitive development. In this study, researchers focused more on aspects of early counting ability because Busy Box media can be used as a learning medium to stimulate children's cognitive development, including the introduction of number concepts, size, shape, and patterns. Children's ability and interest in counting in children aged 5–6 years at PAUD Nusa Indah Ceria East Jakarta is not well developed, so it is not in accordance with their developmental stages. This study aims to investigate the effect of using Busy Box media as learning media on improving the ability to count from the beginning in children aged 5–6 years at PAUD Nusa Indah Ceria East Jakarta. The experimental research method was used in this study, with the experimental group involved in learning using Busy Box media. Data were collected through observation of children's beginning counting ability before and after treatment. The population of this research is PAUD Nusa Indah Ceria East Jakarta. The sampling technique used in this study was quota sampling. The sample in this study were children aged 5–6 years at PAUD Nusa Indah Ceria East Jakarta, as many as 31 children. The results showed that the use of Busy Box media as a learning medium had a significant positive effect on the introduction of science for children aged 5–6 years. It is known that if the value of Sig. (2-tailed) is 0.002 <0.05, then H0 is rejected and H1 is accepted. So it can be concluded that there is an average difference between the introduction of science pre-test and post-test, which means that there is an effect of Busy Box media on the ability to count the beginnings of children aged 5–6 years at PAUD Nusa Indah Ceria, East Jakarta.